1984
DOI: 10.1007/bf00548771
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of midazolam in the aged

Abstract: The pharmacokinetics of midazolam, an imidazo-benzodiazepine derivative, have been studied in 13 subjects over the age of 60 years who received the drug intravenously (0.07 mg kg-1) as an induction agent for endoscopy. Two to three days later, 6 of these subjects received 5 mg of midazolam intramuscularly, and another 6 of the subjects received 10 mg of the drug orally. The plasma concentration-time curves were again studied pharmacokinetically. After intravenous dosing, the mean (+/- SD) elimination half-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 5 publications
4
14
0
Order By: Relevance
“…Old age has been shown to alter the metabolism of several CYP3A substrate drugs, including a number of benzodiazepine derivatives (Greenblatt et al, 1989;von Moltke et al, 1995a;Cotreau et al, 2004). According to some studies, the clearance of the CYP3A substrate midazolam is reduced in healthy elderly subjects (Greenblatt et al, 1984;Smith et al, 1984). Studies have also shown age-related changes in the metabolism of alprazolam and TRZ (Greenblatt et al, 1983a(Greenblatt et al, ,b, 1991Bertz et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Old age has been shown to alter the metabolism of several CYP3A substrate drugs, including a number of benzodiazepine derivatives (Greenblatt et al, 1989;von Moltke et al, 1995a;Cotreau et al, 2004). According to some studies, the clearance of the CYP3A substrate midazolam is reduced in healthy elderly subjects (Greenblatt et al, 1984;Smith et al, 1984). Studies have also shown age-related changes in the metabolism of alprazolam and TRZ (Greenblatt et al, 1983a(Greenblatt et al, ,b, 1991Bertz et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In several European countries, a tablet form is available for oral use as a sedative-hypnotic. The disposition of midazolam has been studied extensively in healthy subjects after intravenous, intramuscular and oral administration (Allonen et al, 1981;Avram et al, 1983;Bornemann et al,1985Bornemann et al, , 1986Greenblatt et al, 1984;Heizmann & Ziegler, 1981;Heizmann et al, 1983;Holazo etal., 1988;Klotz & Zeigler, 1982;Smith et al, 1981Smith et al, , 1984. Midazolam is bound extensively to plasma proteins (94-96%), it has a large volume of distribution (0.8 to 1.91 kr-'), a high systemic clearance (0.24 to 0.731 h-kg-1) and a short elimination half-life (1.5 to 3 h).…”
Section: Introductionmentioning
confidence: 99%
“…It is well appreciated that aging increases the sensitivity to the sedative effects of midazolam and prolongs the duration of its action [1][2][3][4][5][6]. The increasing pharmacodynamic sensitivity due to aging has been explained by EEG data [1], the dose for disappearance of reaction to verbal commands [2], and psychometric tests [3].…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacodynamics and pharmacokinetics of benzodiazepine in the elderly have been reported to differ from those in younger individuals [1][2][3][4][5][6]. Accordingly, excessive sedation and delayed recovery from conscious sedation can occur in the elderly.…”
Section: Introductionmentioning
confidence: 99%